Knowledge and Adoption Levels of Buckwheat (Fagopyrum esculentum) Cultivation by Farmers in Ladakh - Kumar, Yogesh; Angmo, Kunzes (Indian Journal of Extension Education, 2022)
Buckwheat belongs to the family polygonaceous is a high-value crop of Ladakh where it is grown either as the main season crop or after barley as short duration second crop. In the present investigation, four villages were selected from Leh and Kargil, districts. A random sample of 200 farmers was selected that included 50 farmers from each village. Collective interpolation of surveyed data indicated that the maximum number of farmers had a medium level of knowledge and adoption about the cultivation of buckwheat. The main constraints revealed by the respondents about the cultivation of buckwheat crops included nonavailability of improved seeds, lack of knowledge about varieties, lack of knowledge about the market rate, etc. However, the Ladakh administration is now facilitating the cultivation of buckwheat by giving training to the farmers through agriculture university experts and other allied departments in the cold desert aimed to enhance the knowledge base and the adoption of buckwheat cultivation, its popularization and commercialization.